2020
DOI: 10.21203/rs.2.24685/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole blood transcriptomic investigation identifies long non-coding RNAs as regulators in sepsis

Abstract: Background: Sepsis is a fatal disease referring to the presence of a known or strongly suspected infection coupled with systemic and uncontrolled immune activation causing multiple organ failure. However, neither pathogenic long non-coding RNAs (lncRNAs) nor biological network analysis in sepsis draws enough attention to the society of sepsis studies. Methods: We performed an in-silico investigation of the gene coexpression pattern for the patients response to all-cause sepsis in consecutive intensive care uni… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Many studies have reported the genome-wide expression profiling of sepsis [ 13 , 16 , 17 ]. The differential gene expression has been well characterized between sepsis versus non-sepsis inflammatory responses [18] , survivors versus non-survivors [ 19 , 20 ], and sepsis of viral versus bacterial causes [21] . Two endotypes of sepsis were identified [ 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the genome-wide expression profiling of sepsis [ 13 , 16 , 17 ]. The differential gene expression has been well characterized between sepsis versus non-sepsis inflammatory responses [18] , survivors versus non-survivors [ 19 , 20 ], and sepsis of viral versus bacterial causes [21] . Two endotypes of sepsis were identified [ 20 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs may regulate the biological function of miRNAs by acting as competitive endogenous RNAs (ceRNAs) ( Liu et al, 2018 ; Cheng et al, 2020 ). Prior findings have indicated that miR-194-5p regulates apoptosis and genes targeted by miR-194-5p are enriched in apoptotic and inflammatory cell pathways, such as MAPK ( Wang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…High‐throughput gene expression data have been widely applied to characterize the global expression patterns to understand the molecular mechanisms (Cheng et al ., 2016a; Cheng et al ., 2016b; Liu et al ., 2019; Cheng et al ., 2020; Liu et al ., 2020c). We sought to leverage the available senescence transcriptomics datasets to provide independent support for the involvement of the identified ARMs in autophagy.…”
Section: Methodsmentioning
confidence: 99%